Gate-Tunable Graphene/ZnO-Based Dual- Channel Field-Effect Transistor Gas Sensor for Simultaneous Detection of CO2and NO2Gases - Kim, Sihyeok; Singh, Gurpreet; Kim, Youngchul; Park, Jeongwoong; Jeon, Il; Ahn, Yeonghwan; Lee, Keekeun (IEEE Sensors Journal, 2023)
In this study, we have developed a gate-tunable dual-channel field-effect transistor (FET) gas sensor integrated with a microheater and a temperature sensor for the simultaneous detection of CO2 and NO2 gases. In the developed gas sensor, graphene and ZnO were used as two separate sensing channels. Both channels share a single source, and a heavily boron-doped Si substrate is used as a back gate; furthermore, two separate drains are used for both channels via three wire method to eliminate the line resistance effect. The graphene-based channel is used for the selective detection of NO2 gas, whereas the ZnO channel is used for the detection of CO2 gas. To maintain and monitor a constant temperature around the sensing materials, the FET was integrated with the microheater and temperature sensor. It has been observed that the optimal thermal annealing of the graphene/ZnO-based FET in an oxygen environment significantly improves the response of graphene and ZnO toward NO2 and CO2, respectively. By modulating the back-gate voltage, we successfully tune the Fermi level of graphene, which eventually improves the rate of charge transfer between graphene and the NO2 molecules and thus the response. Thus, the versatility of the sensor is demonstrated. The sensing data showed that a positive back-gate voltage enhances the charge transfer rate between graphene and NO2, resulting in a significant improvement in the graphene response. The reverse trend is observed in the ZnO channel, where an eightfold increase in response to CO2 is observed when the gate voltage is changed from 10 V to -10 V, indicating that negative gate voltage enhances the response of ZnO toward CO2 gas. A suitable empirical model is proposed to understand the gate-modulated response of ZnO/graphene. These findings lay the foundation for fabricating the next-generation advanced gas sensors that simultaneously detect toxic gases and monitor air pollution.
Keywords: null; > Field-effect transistor; Gas; II-VI semiconductor material; Xmlns:mml=; Xmlns:xlink=; Xmlns:xsi=; Gate modulation; graphene; microheater; toxic gases; ZnO